The structural, magnetic and electrical properties of chromium doped calcium ferrite nanoparticles - R. UmashankaraRaja; H.C. Manjunatha; Y.S. Vidya; E. Krishnakanth; R. Munirathnam; K.M. Rajashekara; S. Manjunatha (Chemical Physics Impact)
Calcium ferrite nanoparticles doped with Chromium (10-50 mol %) are synthesized using the solution combustion method, employing citrus Lemon extract as a reducing agent, followed by a calcination process at 500oC. Various characterization techniques are employed on the calcined samples. The Bragg reflections resulting from Chromium doping confirm the formation of a singular orthorhombic calcium ferrite phase. Crystallite sizes determined using both Scherrer’s and W-H plot methods found to be decreases with increase in dopant concentration. The surface morphology showcases agglomerated nanoparticles with irregular shapes and sizes, accompanied by pores and voids. The energy band gap found to be increases with increase in dopant concentration from 2.82 to 2.93 eV. The hysteresis loop analysis provides magnetic parameters including saturation magnetization (Ms), remanence (Mr), and coercivity (Hc). As the dopant concentration increases, Ms and Hc found to be maximum at 30 mol% cr3+ concentration in CaFe2O4 NPs. Linear increase in frequency-dependent conductivity at lower frequencies was observed. The presence of semicircles at low frequencies signifies compliance with the Cole-Cole formula for impedance behavior. Additionally, a detailed discussion on dielectric properties is presented. Notably, the dielectric constant decreases from 4.2 to 2.74 with an increase in dopant concentration. These distinctive attributes position the samples as suitable candidates for memory devices as well as high-frequency device applications.